An Investigation into Teacher Wellbeing During the Teacher Training Year - Turner, Sarah; Zanker, Nigel; Braine, Maggie (Design and Technology Education: An International Journal, 2012)
For those studying for the Post Graduate Certificate in Education (PGCE), the teaching practice placement can be a daunting experience. Trainee teachers have to adjust into a new workplace and a complicated professional role which can be stressful; this can result in teachers leaving the profession in their early years if they do not equip themselves with coping strategies and display resilient behaviour. The aims of this study were to gain a deeper understanding of how a cohort of science and design and technology PGCE students settled into schools on their teaching placement and to investigate any differences between mature trainees (those who had taken at least one gap year after their undergraduate degree) and those who have continued straight through their education. Two questionnaires (pre n= 42; post n=48) and a voluntary interview (n=7) were used. Many trainees described their experience as rewarding, yet exhausting and challenging. However, the interviews highlighted there was some erosion of their personal ‘self’ at this early stage of their career. This resulted in, for example, changes in their sleep, eating and exercise patterns and an impact on their relationships.